2008
DOI: 10.1186/1746-160x-4-22
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of various bioabsorbable and nonresorbable barrier membranes for guided tissue regeneration

Abstract: BackgroundDifferent types of bioabsorbable and nonresorbable membranes have been widely used for guided tissue regeneration (GTR) with its ultimate goal of regenerating lost periodontal structures. The purpose of the present study was to evaluate the biological effects of various bioabsorbable and nonresorbable membranes in cultures of primary human gingival fibroblasts (HGF), periodontal ligament fibroblasts (PDLF) and human osteoblast-like (HOB) cells in vitro.MethodsThree commercially available collagen mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 23 publications
1
67
0
1
Order By: Relevance
“…Indeed, the present study demonstrated its ability to (1) fix membranes in wells; (2) divide wells into two compartments (with and without cells) allowing the evaluation of the barrier effect; (3) create an easy access to both faces of the membrane for evaluation; (4) allow access to the under membrane space for several medium changing and long-term evaluation, with the possibility of adding cells at chosen times. Other models previously described in the literature ensured the fixation of the membrane, but they did not allow the evaluation of both faces of the membrane independently and thus the evaluation of the barrier effect (Kasaj et al 2008;Payne et al 1996;Rothamel et al 2004;Takata et al 2001a, b;Wang et al 2002). Only one model was proposed to measure this effect, but it does not permit medium changing and longterm evaluation (Milella et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the present study demonstrated its ability to (1) fix membranes in wells; (2) divide wells into two compartments (with and without cells) allowing the evaluation of the barrier effect; (3) create an easy access to both faces of the membrane for evaluation; (4) allow access to the under membrane space for several medium changing and long-term evaluation, with the possibility of adding cells at chosen times. Other models previously described in the literature ensured the fixation of the membrane, but they did not allow the evaluation of both faces of the membrane independently and thus the evaluation of the barrier effect (Kasaj et al 2008;Payne et al 1996;Rothamel et al 2004;Takata et al 2001a, b;Wang et al 2002). Only one model was proposed to measure this effect, but it does not permit medium changing and longterm evaluation (Milella et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Yet they do not allow the evaluation of both faces of the membrane independently, and thus the barrier effect. For example several authors use double-faced adhesive tape on the floor of the wells (Kasaj et al 2008;Takata et al 2001a;Wang et al 2002). Some other authors used either minu-sheet-rings (Minucells and Minutissue Vertriebs GmbH, Bad Abbach, Germany) used in 24-well plates (Rothamel et al 2004), or membranes under agarose, or half-covered with paraffin (Payne et al 1996;Takata et al 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…The search for adequate materials for membranes that can be applied to bone tissue regeneration has led to the development of a new category of polymers that do not require the second membrane removal stagebioabsorbable polymers (4). Implants containing this type of polymer are used in several applications, such as support for cell cultures, artificial skin and organ growth, surgical sutures, and controlled drug release, among others (5).…”
mentioning
confidence: 99%
“…It has been studied in animal models, in cell culture experiments and even in clinical use [6]. Another absorbable membranes such as alginate, polylactic acid, polygalactin, and collagen were also been introduced for application in GBR procedure [1,3,7]. They do not require secondary surgery, furthermore, reduced cost, decreased tissues morbidity and limited risk of newly bone are the characteristics of bioabsorbable membranes [3].…”
Section: Introduction * * * *mentioning
confidence: 99%